A Review of the Problems and Challenges for Conservation of Tigers in Similipal Tiger Reserve, Orissa, India - Rout, S. D.; Sharma, Jitendra (Indian Forester, 2008)
Similipal Tiger Reserve , one of the initially created nine tiger reserves in the country, is the largest single contiguous patch of tropical forest located in the State of Orissa. The ever increasing biotic pressure due to presence of 65 villages inside the sanctuary and 1,200 villages around 10 km of its boundary is a potential threat to its existence. A balance has to be struck between development and conservation. Minimum biotic interference can not be avoided to maintain the sanctity and natural wealth of this biodiversity rich biome. Some protection initiatives have been taken to overcome several problems and to strengthen for the conservation of tiger and other animals in Similipal Tiger Reserve, Orissa.